Compulsory licensing of patents as a response to the COVID-19 Pandemic? The case of the Andean Community - Sasaki Otani, María Ángela (2022)
The purpose of this article is to address, from the point of view of regional integration, some of the problems emerging from the COVID-19 pandemic with the aim of imagining a new path or route to follow. To this end, within the framework of the Andean Community (CAN), we recall the specific objectives and main functions of the Andean Health Organization (ORASCONHU). In addition, we focus on the access to health of Andean citizens in the light of the Andean Community Law, analyzing the figure of compulsory licensing of invention patents as a possible response to the COVID-19 pandemic.